Effect of biaxial fabric prestressing on the mechanical properties of plain–weave E–glass/polyester composites - Mostafa, Nawras Haidar (2017)
It is of interest whether induced residual stresses would affect the mechanical properties of fibre–reinforced composites. One of the methods that can be used for altering the induced residual stresses within the matrix is the method of fibre prestressing. Although this method was previously used for developing the mechanical properties of unidirectional composites, its application to the woven composites was very rare. There are many applications of composite materials where woven fabric has been used instead of unidirectional fibre such as for helmets, armours, boats, and the automotive components. The mechanical properties of woven composite may be improved without increasing its volume and/or weight. Therefore, this study emphasizes on improving the mechanical properties and fatigue behaviour of the plain–weave composite by applying biaxial fabric prestressing.